The Evolving Domain of Entrepreneurship Research - Bo Carlsson; Pontus Braunerhjelm; Maureen McKelvey; Christer Olofsson; Lars Persson; Håkan Ylinenpää (Research Institute of Industrial Economics (IFN), 2013)
Research on entrepreneurship has flourished in recent years and is evolving rapidly. This paper explores the history of entrepreneurship research, how the research domain has evolved, and its current status as an academic field. The need to concretize these issues stems partly from a general interest to define the current research domain, partly from the more specific tasks confronting the prize committee of the Global Award for Entrepreneurship Research. Entrepreneurship has developed in many sub-fields within several disciplines primarily economics, management/business administration, sociology, psychology, economic and cultural anthropology, business history, strategy, marketing, finance, and geography representing a variety of research traditions, perspectives, and methods. We present an analytical framework that organizes our thinking about the domain of entrepreneurship research, by specifying elements, levels of analysis and the process/context. An overview is provided of where the field stands today and how it is positioned relative to the existing disciplines and new research fields upon which it draws. Areas needed for future progress are highlighted, particularly the need for a rigorous dynamic theory of entrepreneurship that relates entrepreneurial activity to economic growth and human welfare. Moreover, applied work based on more careful design as well as on theoretical models yielding more credible and robust estimates seems also highly warranted.
Keywords: B00; L26; M13; O10; 330; Entrepreneurship research; Evolution; Academic disciplines; Global Award for Entrepreneurship Research